Pengaruh Kualitas Audit Dan Komite Audit Terhadap Kualitas Pelaporan Keuangan Perusahaan Yang Terdaftar Di Jakarta Islamic Index (JII) - Liya Ermawati; Yulistia Devi Devi; Naurah Nazhifah Arramadani (Jurnal Akuntansi dan Keuangan, 2020)
The current era of free trade globalization, companies are led to present financial reporting that can provide information needed by users. With the company presenting financial reporting, the company's economic conditions can be known by outside parties. The quality of financial reporting is related to the overall performance of the company which is reflected in corporate profits and the performance of the company's capital market which is realized in the form of rewards. Every company must have audit quality, because all operational activities in the company have a set standard in order to achieve the company's goals and objectives. The Financial Accounting Standard Board (FASB) has realized that the audit committee (internal auditor) has involvement in the financial reporting process and actively contributes to creating more effective corporate governance practices. The audit quality function functions to oversee management together with the audit committee. In good corporate governance, the resulting financial reporting is even better. The Government of Indonesia in 2000 issued a sharia stock index, the Jakarta Islamic Index (JII). The Jakarta Islamic Index (JII) is a sharia stock index consisting of 30 most liquid stocks of issuers whose business activities do not conflict with sharia principles. the performance of the Jakarta Islamic Index (JII) began to be seen in 2018 where its performance exceeded the performance of the JCI where during the last six years the performance of the JCI has always been above the performance of the Jakarta Islamic Index (JII). This study aims to analyze the effect of audit quality on the quality of financial statements, the influence of the audit committee on the quality of financial statements and the effect of audit quality and the audit committee together on the quality of financial statements of companies listed on the Jakarta Islamic Index (JII). The sample of this study consisted of 30 companies registered in the Jakarta Islamic Index (JII) in 2016-2017 which were determined through purposive sampling, this study used multiple regression analysis techniques. The results show that: a) audit quality affects the quality of financial reporting; b) the audit committee has no effect on the quality of financial reporting; and c) simultaneously audit quality and audit committee influence the quality of financial reporting.